2018
DOI: 10.1007/s00192-018-3849-2
|View full text |Cite
|
Sign up to set email alerts
|

Expectations regarding eHealth among women with stress urinary incontinence

Abstract: Introduction and hypothesisStress urinary incontinence (SUI) is a common condition with a major impact on quality of life (QoL). Various factors prevent women from seeking help. However, eHealth (Internet-based therapy) with pelvic floor muscle training (PFMT) is an effective and satisfying intervention for these women. We hypothesize that women with symptoms after regular therapy will profit from eHealth. This study explores the expectations regarding an eHealth intervention among women who still suffer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…For these women the standalone character of the e-Health intervention was a barrier to adopt it. The wish for contact is in line with previous studies [ 15 , 19 , 20 ] although Asklund et al found a lower need in women using a mobile app, reflected by their overarching theme entitled ‘Enabling my independence’ [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For these women the standalone character of the e-Health intervention was a barrier to adopt it. The wish for contact is in line with previous studies [ 15 , 19 , 20 ] although Asklund et al found a lower need in women using a mobile app, reflected by their overarching theme entitled ‘Enabling my independence’ [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
“…Key topics that were addressed were: reasons for participation, previous experiences with treatment for SUI, expectations prior to the start of the intervention, effects of the intervention, performing and prioritizing PFMT in daily life, adherence and technical aspects of the intervention. We explicitly asked women about their experiences with unsupervised treatment, because literature shows that women feel the need to meet with someone during the training program [ 15 ]. After seven interviews, we adjusted the interview guide [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the expectations and experiences of women concerning eHealth applications for UI [18] identified only one study of an online self-help program with email support of stress UI [19]. Recently, studies have been published on eHealth for women with stress UI, including their expectations of eHealth [20] and their experiences of an app focused on pelvic muscle training [21]. Notably, the two studies on experience with eHealth identified themes that overlapped considerably with those in our study [19,21].…”
Section: Discussionmentioning
confidence: 51%
“…The complexity of mHealth interventions with multiple interacting components calls for a thorough evaluation of the connection between patient experience, adherence, and effectiveness but is often lacking [ 5 , 6 ]. Previous qualitative studies of women suffering from urinary incontinence have identified factors that could affect app- or internet-based treatment for urinary incontinence by exploring their expectations and experiences [ 7 - 10 ]. Women expected that internet-based treatment would be more accessible, more flexible, and improve treatment adherence, but they expressed concern about the lack of contact with a caregiver [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%